Informative treatment of the mapuches in the newspaper El Mercurio. A content analysis based on the Framing Theory - Del Valle-Rojas, Carlos (2019)
This paper analyzes the information treatment of the Mapuche people in the newspaper El Mercurio during two periods. First, between 1950 and 1973 (twentieth century); and second, during the years 2010, 2013 and 2014, (21st century). To this end, a corpus of 340 journalistic texts has been selected, of which 147 correspond to the 20th century (1950-1970) and 193, to the 21st century (2010, 2013-2014). The analysis shows that most of the frames are linked to conflicts, criminal prosecutions and arson attacks; so that El Mercurio prioritizes connotations and negative events to inform about the Mapuche indigenous people.